Prominence Patterns in a Second Language: Intonational Transfer From Dutch to Spanish and Vice Versa. Issue 1 (8th October 2015) - van Maastricht, Lieke; Krahmer, Emiel; Swerts, Marc
Abstract : This research describes the production of prosodic cues to mark information structure in Spanish and Dutch. It compares speech by native (L1) and second language (L2) speakers and investigates prosodic transfer from the L1 to the L2, L2 proficiency as a factor in transfer effects, and transfer from the L2 to the L1. The results confirm that Spanish and Dutch natives use different prosodic cues to mark information status. Comparison of L1 and L2 data reveals that these prosodic differences lead to transfer from the L1 to the L2. The proficiency level of the speaker modulates transfer effects. To some degree, pitch accents used to mark focus appear to be transferred from the L2 to the L1 as well.